Size and symmetry of trunk muscles in ballet dancers with and without low back pain - Gildea, J. E.; Hides, J. A.; Hodges, P. W. (Journal of Orthopaedic & Sports Physical Therapy, 2013)
STUDY DESIGN: Cross-sectional, observational study. OBJECTIVES: To investigate the cross-sectional area (CSA) of trunk muscles in professional ballet dancers with and without low back pain (LBP). BACKGROUND: LBP is the most prevalent chronic injury in classical ballet dancers. Research on nondancers has found changes in trunk muscle size and symmetry to be associated with LBP. There are no studies that examine these changes in ballet dancers. METHODS: Magnetic resonance imaging was performed in 14 male and 17 female dancers. The CSAs of 4 muscles (multifidus, lumbar erector spinae, psoas, and quadratus lumborum) were measured and compared among 3 groups of dancers: those without LBP or hip pain (n = 8), those with LBP only (n = 13), and those with both hip-region pain and LBP (n = 10). RESULTS: Dancers with no pain had larger multifidus muscles compared to those with LBP at L3-5 (P<.024) and those with both hip-region pain and LBP at L3 and L4 on the right side (P<.027). Multifidus CSA was larger on the left side at L4 and L5 in dancers with hip-region pain and LBP compared to those with LBP only (P<.033). Changes in CSA were not related to the side of pain (all, P>.05). The CSAs of the other muscles did not differ between groups. The psoas (P<.0001) and quadratus lumborum (P<.01) muscles were larger in male dancers compared to female dancers. There was a positive correlation between the size of the psoas muscles and the number of years of professional dancing (P = .03). CONCLUSION: In classical ballet dancers, LBP and hip-region pain and LBP are associated with a smaller CSA of the multifidus but not the erector spinae, psoas, or quadratus lumborum muscles.